HUBUNGAN LAMA DUDUK DENGAN LOW BACK PAIN PADA KARYAWAN PT.INSANI MEDICAL CENTER - Ruth Cahaya Tiarma (2022)
Low back pain is a sensory experience being the main problem of physical restriction for work. Sitting for long periods of time and improper body position at work can strain the lower back muscles. Internal and external factor usually increase their problem. Objective: This study aims to determine the relationship between long sitting position with low back pain for Pt.Insani Medical Center. Methods:. This study uses an observational quantitative method with a cross-sectional approach. A total of 50 employees of PT. Insani Medical Center participated in this study. This research instrument uses a long sitting questionnaire to determine the duration of the respondent's sitting at work, and the Owestry Disability Index questionnaire to determine the respondent's pain and disability level. Results: based on the results of data processing using SPSS 25, 92.0% respondents experienced minimal pain and 8% respondents experienced moderate pain. After the correlation test, the correlation coefficient of Spearmen's Rho sitting and low back pain was obtained, p = 0.37 with a significance value of p = 0.799. Conclusion: There is no relationship between long sitting and low back pain in employees of PT. Insani Medical Center.